Fotometría de Cúmulos Estelares en el OAUNI - Pereyra, Antonio (2019)
In this work we present preliminary analysis of the astronomical photometry program for stellar clusters observed at OAUNI on the last years. Up to date twelve open clusters and nine globular clusters have been observed, in general, in more than one broadband filter. Multicolor photometry for selected clusters is shown along with a color-magnitude diagram for one open cluster. These measurements are the first ones of their kind collected by a peruvian astronomical facility.